Immersive Virtual Reality in Improving Communication Skills in Children with Autism - Halabi, Osama; Elseoud, Samir A.; Alja'am, Jihad M.; Alpona, Hena; Al-Hemadi, Moza; Al-Hassan, Dabia (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Individuals in the Autism Spectrum often encounter situations where they have to respond to questions and situations that they do not know how to respond to, such as, questions asked by strangers including ones related to daily-life activities. A variety of research has been done to improve social and communication impairments in children with autism using technology. Immersive virtual reality is a relatively recent technology with a potential to bring an effective solution and used as a therapeutic tool to develop different skills. This paper presents a virtual reality solution to reduce the gap experienced by autistic children due to their inability to establish a communication. An interactive scenario-based system that uses role-play and turn-taking technique was implemented to evaluate and verify the effectiveness of immersive environment on the social performance of an autistic child. Preliminary testing of the system demonstrated the feasibility of VR-based system as a took for improving the communication skill in Autism Spectrum Disorder (ASD) children. The results of the comparative usability study show the effectiveness of immersive VR in motivating and satisfying the autistic.